Flame and fodder: how fire and grazing shape arthropod communities in the Okavango Delta - Grobler, Michiel (Department of Biological Sciences, 2024)
The documentation of species presence and distribution is essential for the conservation of biodiversity worldwide. Invertebrates are relatively understudied compared to vertebrates, globally and within the southern African region. This is especially true for developing countries, due to accessibility, costs associated with remote fieldwork and lack of taxonomic expertise. Nevertheless, southern Africa is highly diverse in fauna and flora, and many species still are undescribed in many of the countries in this region. In Botswana, the Okavango Delta is an exceptionally unique biological system with a vast wetland in the middle of the Kalahari basin, acting as one of the only consistent water resources. The complexity of this flood-driven system is not only due to seasonal influxes from the catchment area in central Angola, but also due to the slow drop in elevation, which causes complex channels, streams, bogs and other aquatic habitats to form as the delta fans out towards the Makgadikgadi pans. At the core of this critical hydrological system lie aquatic and terrestrial systems and processes that ensure its continued functioning and overall health, with many of these services underpinned by invertebrates, arthropods in particular. Although the aquatic invertebrates are relatively well-studied, the terrestrial arthropods have received less attention, while undoubtedly also providing critical regulatory services on the islands within the Delta, and along the edges. As a World Heritage Site, the Okavango Delta should be prioritised for research related to ecosystem processes and monitoring of the smaller faunistic “cogs” that ensure the collective functioning of the overall system, especially due to the threats it faces. Anthropogenic disturbances have become more common and regular along the edges and within the Okavango Delta over the last few decades, and as such, human-induced fire and livestock grazing has increased the pressure on the natural systems in which it occurs. Given the fragmented knowledge of terrestrial arthropods within Botswana, and the Okavango Delta specifically, this study aimed to compare arthropod communities between ongoing disturbance regimes, using a multi-taxon approach. Specifically, this study aimed to: 1) compare the diversity and abundance of four terrestrial arthropod groups (ants, wasps, springtails and spiders) in burnt and grazed sites, 2) investigate whether burning or grazing have impacts on arthropod diversity, in terms of species richness and abundance, 3) provide a starting point dataset to monitor the impact of disturbances on arthropod communities in the Okavango Delta into the future, 4) generate starting point species inventories for these four taxa in this region, and 5) compile an updated species list of the spiders (Araneae) of Botswana. Using pitfall traps and litter extractions across two seasons, the abundance of the four groups was only fractionally higher in the wet season for the pitfall traps, but litter extractions had large increases in ants, springtails and wasps in the wet season. Ants had the most species and the highest diversity in the grazed sites compared to burnt sites, while Collembola and Araneae communities were more even in the burnt sites than in the grazed sites. Species richness, evenness and diversity varied between trapping methods and between groups studied, illustrating the varied responses of arthropod communities to disturbances. Ants and Collembola varied significantly between seasons, but not between disturbance types, while wasps and spiders differed significantly between both season and disturbance types. This study created the first starting point dataset for comparing the impacts that disturbances have on arthropod community shape and composition. An up-to-date species list for spiders of the Okavango Delta was compiled, adding 37 new records to the existing species list. From pitfall traps and litter extractions a total of 20 families and 51 genera were sampled, with 40 species identified. From active collections, a total of 18 families, 55 genera and 70 species were collected. The updated species list of spiders in the Okavango Delta contains 33 families, 141 genera and 220 species. This will serve as the basis for further species inventories and diversity studies in the region. It is recommended that terrestrial arthropod research be continued within this World Heritage Site to ensure the documentation of the diversity of species present here, but also to utilize these species as indicators for ecosystem changes to ensure the continued survival of this wetland and the species that depend on it.